Neuroticism, cancer mortality salience, and physician avoidance in cancer survivors: Proximity of treatment matters. Issue 4 (7th November 2021) - Boyd, Patrick; Murray, Ashley B.; Hyams, Travis; Sleight, Alix G.; Moser, Richard P.; Arndt, Jamie; Czajkowski, Susan M.; Hall, Kara
Abstract: Objective: To examine if the relationship between neuroticism and physician avoidance/physician visit concerns are mediated by perceptions that cancer is associated with death ("cancer mortality salience"; CMS) for cancer survivors to inform public health interventions and tailored health communications. Methods: Cancer survivors comprised 42.3% of the total sample ( n  = 525). Participants completed a 4‐item neuroticism scale, 4‐item cancer perceptions scale, and 4‐item physician avoidance and concerns scale. Multiple linear regression models were used to assess relationships among variables for cancer survivors and separately for those without a history of cancer. Results: Neuroticism was positively associated with CMS for cancer survivors, b  = 0.26, ( p  < 0.001), and those without cancer, b  = 0.22, ( p  < 0.001). There was an association between neuroticism and physician avoidance among cancer survivors with temporally distant treatment courses after controlling for CMS, b  = 0.56 ( p  = 0.006), but not for those currently or recently having had undergone treatment ( p  = 0.949). There was also an indirect relationship between neuroticism and physician visit concerns that was mediated by CMS for cancer survivors, b  = 0.07, CI = [0.03, 0.13], but this relationship was again driven by cancer survivors with more distal treatment courses. Conclusions: High neuroticism in cancer survivors is associated with physician avoidance and physician visit concerns when treatment is temporally distant. Interventions aimed at decoupling the association between cancer and death can help increase the willingness of cancer survivors to attain cancer care follow‐ups and healthcare more generally.